2022
DOI: 10.3389/fpls.2022.877695
|View full text |Cite
|
Sign up to set email alerts
|

Combining Metabolomics and Transcriptomics to Reveal the Mechanism of Coloration in Purple and Cream Mutant of Sweet Potato (Ipomoea batatas L.)

Abstract: Purple sweet potato is considered as a healthy food because of its high anthocyanins. To understand the coloring mechanism and quality change between purple-fleshed sweet potato (cv. Xuzi201) and its cream fleshed mutant (M1001), a combined metabolomic and transcriptomic analysis was performed. The metabolome data showed that 4 anthocyanins, 19 flavones, 6 flavanones, and 4 flavonols dramatically decreased in M1001, while the contents of 3 isoflavones, 3 flavonols, 4 catechins, and 2 proanthocyanins increased.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
4
1
Order By: Relevance
“…Nevertheless, the significantly differentiated central anthocyanin metabolic network between the purple and non-purple sweet potato materials still sheds light on the anthocyanin component divergence. In our study, 14 categories of anthocyanin, including one glycosylated pelargonidin, one glycosylated petunidin, one malvidin, five glycosylated peonidin, and six glycosylated cyanidin, were recognized, whereas there were only seven or eight kinds identified in a previous study Zhang et al, 2022). Despite the technical difficulty in accurately verifying the monomer of anthocyanin (Li et al, 2012), we still detected more glycosylated derivatives in the purple sweet potatoes DZ88 and DZ54 (Table 1), which all displayed higher accumulation than the others.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Nevertheless, the significantly differentiated central anthocyanin metabolic network between the purple and non-purple sweet potato materials still sheds light on the anthocyanin component divergence. In our study, 14 categories of anthocyanin, including one glycosylated pelargonidin, one glycosylated petunidin, one malvidin, five glycosylated peonidin, and six glycosylated cyanidin, were recognized, whereas there were only seven or eight kinds identified in a previous study Zhang et al, 2022). Despite the technical difficulty in accurately verifying the monomer of anthocyanin (Li et al, 2012), we still detected more glycosylated derivatives in the purple sweet potatoes DZ88 and DZ54 (Table 1), which all displayed higher accumulation than the others.…”
Section: Discussioncontrasting
confidence: 54%
“…Hence, the reallocation of intermediate substrates, which was largely determined by the expression of specific genes (e.g. FLS), demonstrated that the transcriptional discrepancy in the gene expressions and the gene-metabolite interactions might have played a crucial role in the metabolite flux repartitioning, which thereafter caused the distinct pigmentary performances in the purple and non-purple sweet potatoes (Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 33 isoflavones from peas were detected in this study, and most of them were much richer in dried peas than fresh peas, but sophoricoside, genistein-7-O-galactoside, and 4′,5-dihydroxyisoflavone-7-O-galactoside were accumulated in fresh peas (Figure 5). Moreover, we summarized the kinds and numbers of isoflavones from fruits [43,44], staple food crops [1], coarse cereals [18,45], tuber crops [46][47][48], and vegetables [49][50][51][52][53] in recent reports. They were characterized using the same metabolomic detection platform of MetWare.…”
Section: Identification and Comparative Analysis Of The Flavonoid Met...mentioning
confidence: 99%
“…Purple sweet potato (PSP) ( Ipomoea batatas L.), a member of the sweet potato family, exhibits an intense purple color in the root and skins owing to the accumulation of anthocyanins [ 1 ]. As one of the most promising economic crops, PSP contains abundant amounts of nutrients.…”
Section: Introductionmentioning
confidence: 99%